FREE DEFORMATION OF MULTIRESOLUTION B-SPLINES CURVES - Rivera, Luis A (2000)
When a point oí the curve is dragged to another position, a local curve segment ís affected, whose size could be determined by propagating the deformation on lower resolution of the curve in multiresolution representation. Therefore, for a given point displacement, different relative local segments can be modífied, by varying local parameters given by a function which simulates a stiffness constant. Using this method, the designer can interactively modify the curve, in a natural manner, by controlling the size of the affected segment, avoiding the use of energy terma for deformation. We have tested our ideas with a prototype system for modeling uniform B-spline curves in multiresolution, using biorthogonal B-spline wavelets.